Catecholamine activation of pyruvate dehydrogenase in white adipose tissue of the rat in vivo. - Kilgour, E (1987)
Intraperitoneal injections of noradrenaline or adrenaline into rats increased the proportion of pyruvate dehydrogenase in the active state in white adipose tissue; this effect of catecholamines was also apparent in streptozotocin-diabetic rats, showing that it was not due to an increase in serum insulin concentration. The catecholamine-induced increase in pyruvate dehydrogenase of white adipose tissue in vivo was completely blocked by prior injection of either the beta-antagonist propranolol or the alpha 1-antagonist prazosin. Cervical dislocation of conscious rats increased pyruvate dehydrogenase activity of white adipose tissue, which was prevented by prior injection of propranolol. Adrenaline (30 nM) activated pyruvate dehydrogenase in white adipocytes in vitro; the maximum effect of adrenaline required activation of both alpha 1- and beta-receptors. The results show that catecholamines activate pyruvate dehydrogenase of white adipose tissue both in vivo and in vitro and that this effect is mediated by a combination of alpha 1- and beta-adrenergic receptors.